STRATEGI MITIGASI UNTUK MENGATASI PENYAKIT AKIBAT SANITASI LINGKUNGAN YANG BURUK : PARADIGMA BARU MITIGASI BENCANA - Mardi Wibowo (BPPT)
Indonesiaâ€™s disaster potential is very high and varied. Natural conditions, population and cultural diversity in Indonesia cause in increased risks due to natural disasters, man-made disasters and emergencies to be complex, on the other side Indonesia is rich in natural resources. Disaster relief should be directed from pre-disaster phase, during emergency response and post disaster. The initial phase of this effort is the need for understanding of all stakeholders (mainly institutions) about the development of the concept and paradigm change mitigation. By knowing the concept and development of this paradigm is expected that all stakeholders can do things from the smallest to the larger and synergies will occur from all stakeholders to minimize the impact of a disaster. From ancient times until now the concept of a paradigm in disaster management shift very rapidly starting from the conventional to the holistic paradigm. In general, the development paradigm is theÂ conventional paradigm (relief & emergency), mitigation paradigm, development paradigm and paradigm of risk reduction. Paradigm that is now growing and effective enough to minimize the risk mitigation is the analogy of mitigation for diseases caused by poor environmental sanitation. The analogy with disease problems mentioned above, there are disasters which can now be viewed in the same perspective, where the current disaster is something that is not predictable and it is destiny or part of the risks of everyday life. The concentration of people and higher population levels worldwide would increase the risk of disasters and multiply the consequences of natural hazards as dangers that arise. However, based on science â€œof epidemiology disasterâ€ actually most of these disasters can be prevented or at least many ways to reduce the impact of a disaster (mitigation actions). Like the war against disease, warfare should be fought against disaster by any person jointly and involve society as well as changes in social behavior as well as improvements in individual practices.Keywords : mitigation, disease, environmental sanitation, disaster